Maternal-Neonatal Serum Albumin Level and Neonatal Respiratory Distress Syndrome in Late-Preterm Infants - Ying, Qian; You, Xue-qin; Luo, Fei; Wang, Ji-mei (Frontiers in Pediatrics, 2021)
Background: To determine the correlation between maternal-neonatal serum albumin level and respiratory distress syndrome (RDS) in late-preterm infants. Methods: This case-control study included 112 late-preterm newborns admitted to the neonatal intensive care unit of our hospital between January 2018 and July 2019. Those infants were divided into the RDS group (n=56) and the non-RDS group (n=56). Levels of maternal-neonatal serum albumin, pregnancy complications, and baseline information of the infants were compared between the two groups. Results: 1. There was no correlation between maternal and neonatal serum albumin measures. The maternal albumin level in the RDS group was lower than that in the control group (33.38±3.31 vs. 33.60±3.31, P>0.05), but the difference was not statistically significant. The neonatal albumin level in the RDS group was significantly lower than that in the control group (32.70±2.48 vs. 35.66±3.27, P<0.05). To predict RDS in late-preterm infants, using the albumin cutoff level of 34 g/L provides a sensitivity of 83.9% with a specificity of 62.5%. 2. Gestational age, primipara, placenta previa, antenatal corticosteroid therapy, delivery mode, and neonatal serum albumin level were associated with RDS in the late preterm infant.3. After adjustment for gestational age, logistic regression analysis showed that neonatal serum albumin level, placenta previa, and delivery mode were independent risk factors for RDS in late-preterm infants. However, albumin level did not related to the severity of RDS. Conclusion: The decrease in serum albumin within the first day after birth was closely related to the occurrence of RDS in late-preterm infants.